A Rebalancing of Financial Valuations and Expectations Moving Forward in the Telehealth Sector as the United States Moves Toward a Post-COVID-19 Reality - Nicholas Bettencourt; Conor John Wilson; Philippa Jaye Johnson; Fabian D'Souza (JMIR Publications, 2023)
The telehealth sector of health care delivery experienced significant growth at the start of the pandemic as web-based care quickly became essential for the ongoing safety of patients and health care providers, such as clinicians and other health care professionals. After vaccines were introduced, however, telehealth companies lost value as the need for web-based care appeared to lessen. Presently, both existing telehealth companies and new entrants to the space are seeking ways to innovate, gain investor and customer buy-in, and overcome competitors. New companies are hoping to be seen not as pandemic-era substitutes, but instead as reinforcements to in-person care, valuable in their own right thanks to the convenience and technological advancements they bring. This struggle to reframe the value proposition, or perceived benefit, of telehealth is reflected in fluctuating stock prices and dropping valuations. This viewpoint summarizes the market volatility seen in the telehealth sector since the start of the COVID-19 pandemic and suggests potential opportunities for growth in the space. This is accomplished through a qualitative secondary research approach, leveraging contemporary sources, financial references such as Yahoo! Finance, and peer-reviewed literature to support predictions for the future market. We found that, in 2020, the size of the US telehealth market rose to US $17.9 billion and is estimated to reach US $140.7 billion by 2030. Additionally, digital health venture funding nearly doubled in 2020 over the prior 2 years with total funding rising to US $14.1 billion. However, these factors produced an oversaturated market in which the volume of supply was higher than demand, resulting in a sharp drop in valuations for some as vaccination rates climbed in 2021. In the face of this rebalancing, or return to normal following excessively high or unsustainable valuations, we suggest a possible path forward for telehealth companies in the postpandemic era. Suppliers' current role in the telehealth space-whether health care industry incumbents, that is, traditional health care delivery systems and companies, or "telehealth-first" challengers-are especially relevant to the specific growth strategies they should pursue. Furthermore, consideration of the areas of medicine and characteristics that best lend themselves to web-based care may lead to a greater chance for long-term success in a postpandemic health care delivery system. In the future, we believe investors should expect a bullish market, that is, one characterized by growing share prices. Success is likely to occur in part through changing the actual models of care, as opposed to moving traditional care to a web-based format. The oversaturated market will likely condense into select established telehealth giants who were able to adapt to the changing landscape. While investors may be reasonably hesitant regarding individual telehealth companies, the industry can expect slowed but continued growth.